Aerial adult dragonflies are highly sensitive to in‐water conditions across an ancient landscape. Issue 1 (19th October 2016) - Kietzka, Gabriella J.; Pryke, James S.; Samways, Michael J.
Abstract: Aim: Adult dragonflies are renowned for being good bioindicators of anthropogenic change, but their response to the heterogeneity of undisturbed river systems has received little investigation. The Cape Floristic Region (CFR) has had a long lineage of natural selection which has honed life stages to the fine grain of the river systems. This leads to the intriguing question: How sensitive are the aerial adults to the in‐water conditions? Location: Rivers of the CFR, in the Western Cape Province, South Africa, are naturally heterogeneous and complex ecosystems running across a geologically ancient landscape. The CFR is a significant centre of local endemism for many taxa, including dragonflies. Methods: We investigated dragonfly assemblages and 20 environmental variables along untransformed reaches of three CFR rivers. Results: We found that each river has its own particular 'signature' dragonfly assemblage. We also found that certain in‐water parameters were the most important factors driving adult dragonfly assemblages, and not variables associated with substrate or riparian vegetation under these historic, natural conditions. This responsiveness to a heterogeneous range of in‐water variables was similar from one river to the next, and also was independent of species turnover among the different dragonfly assemblages. Main conclusions: From a conservation perspective, the natural variation in certain water parameters, particularly in‐water conditions, is essential for supporting the full suite of adult dragonfly species. Challenging but important for conservation planning is that each river has its own biotic merit. Addressing this challenge also means that maintenance and restoration of historic, heterogeneous, in‐water conditions in addition to the removal of alien invasive trees which are already known to be highly detrimental to this largely irreplaceable dragonfly fauna. Prioritizing which rivers to conserve can be achieved through using indices involving dragonflies.